Psychological skills of Malang State University athletes who participate in POMPROV 2022 - Moch. Ghossam Azim; Kurniati Rahayuni; Prisca Widiawati (Universitas Negeri Malang, 2023)
Achievement sports are a form of activity that requires a psychological aspect. The psychological aspect of athletes at the State University of Malang is the key to victory in winning the overall champion of POMPROV 2022. ACSI-28 (Athletic coping stress Inventory-28) is a psychological benchmark in sports achievement, namely (1) coping with advertising; (2) peaking under pressure; (3) goal setting/mental preparation (4) concentration; (5) free from worry; (6) confidence and achievement motivation;